Training On Calculation Of Salon Service Costs For People With Physical Disabilities - Prihastuti, Asepma Hygi; Ramadhani, Suci; Wahyuni, Sri; Adriyani, Annesa; Zainal, Rahmi (Doctoral Program of Social Science, Pasundan University, 2025)
Poverty and economic vulnerability are still significant issues, especially for groups of people with physical disabilities who experience physical limitations. The Riau Province Empowerment of People with Physical Disabilities UPT in Pekanbaru responded to this condition by providing various skills training, one of which is make-up and salon. Training in calculating the cost of salon services as a crucial element for people with physical disabilities who are engaged in this field. This training is relevant because: 1) Increases economic independence and social inclusion by opening up entrepreneurial paths amidst limited access to formal employment and reducing dependency; 2) Utilizes the potential of the stable and flexible salon industry market in Pekanbaru, especially through the home-based business model; 3) Ensures business sustainability through an essential understanding of cost to avoid losses, optimize profits, and facilitate financial planning and management; and 4) Supports local government programs in empowering MSMEs with disabilities. The training methods used are inclusive and adaptive, including interactive face-to-face sessions with visual demonstrations and group discussions, practical approaches through simulations and case studies, as well as guidance and mentoring. The expected outcomes of this training include increased knowledge of cost components and costing methods, business decision making, and increased independence and self-confidence to become entrepreneurs. This training is a strategic investment that equips people with physical disabilities in Pekanbaru to build profitable and sustainable salon businesses, while also encouraging broader social inclusion.